FAST DISSOLVING TABLETS OF PIMOZIDE: DESIGN, OPTIMIZATION AND INVITRO CHARACTERIZATION - Raja Rajeswari Kamisetti; Moses Mekala; Sudhakar Muvvala; Durga Bhavani Penmatsa (Indonesian Journal of Pharmacy, 2015)
As precision of dosing and patient compliance become an important prerequisite for a long-term treatment of Tourette’s syndrome there is a need to develop formulation for this drug, which overcomes problems such as difficulty in swallowing, inconvenience in administration while travelling and patient’s acceptability. The present work was undertaken with a view to develop a fast dissolving tablets of Pimozide  using Kyron T-314 as super-disintegrant along with Avicel PH 102 as diluent by response surface method using direct compression. Drug-excipient compatibility studies were confirmed by FTIR Spectroscopy. The tablets were evaluated for hardness, friability, weight variation, wetting time, disintegration time and uniformity of content and invitro dissolution. Based on evaluating parameters, formulation prepared by using 4.5% Kyron T-314 with 11.5% Avicel PH-102 was selected as optimized formulation and Formulation (F3) had disintegration time of 7.63±0.25s. and percentage cumulative drug release of   81.60 after 10min. The formulations were further studied and confirmed for their stability. Hence it was concluded that direct compression using Kyron T-314 superdisintegrant and Avicel PH 102 was simple and economic technique which can be used for formulation of fast dissolving tablets of Pimozide.Key word: Pimozide, Tourette’s syndrome, fast dissolving tablets, Kyron T 314, direct compression